La soffitta e il rettangolo rosso. Due conversazioni con Massimo Fagioli - Fagioli, Massimo (Il sogno della farfalla, 2017)
In line with the publication of unreleased papers and interventions by Massimo Fagioli, which we started with the last number of our journal, here we propose two interviews which were run by the journalists Giovanna Pezzuoli and Laura Lattuada respectively. The first interview was published in the newspaper Corriere della Sera; the second was broadcast on Arturo TV channel, within the program called Passepartout: ospite a sorpresa (Passepartout: surprise guest). In both cases, Massimo Fagioli was interviewed at his house in Rome, and the dialogue with the interviewer became the occasion to highlight the human reality of the psychiatrist who developed Human Birth Theory and run Analisi collettiva for more than 40 years, and his deep interest in the language of images.